The Analysis of Application Income Tax Article 21 for Business Subject to Final Income Tax at CV RPT - N M S Ambarawati; W H Utthavi; L M Wahyuni (Jurusan Akuntansi Politeknik Negeri Bali, 2020)
This research aims to analyze and determine 1) The application of income tax article 21 on business subject to final income tax at CV RPT, 2) The potential for underpayment of article 21 income tax after calculating according to applicable tax regulations. CV RPT is a company engaged in the construction service business. For taxpayers who are subject to final income tax, benefit in kind given to employees is the object of income tax article 21. The data used in this research are secondary data obtained through observation and documentation. This research uses a quantitative descriptive analysis. Based on the results of the research, there is a potential for underpayment of income tax article 21 on CV RPT, amounting to Rp9.212.540 for permanent employees and Rp2.750.000 for final income tax article 21 on pension benefits. Besides, it also resulted in the potential for the imposition of administrative sanctions in the form of interest due to the still unfulfilled income tax article 21 obligation, namely Rp1.289.756 for underpayment of article 21 income tax for permanent employees and Rp385.000 for final income tax article 21 on pension benefit.